Analisis Perbedaan Revenue Bunga Bank Konvensional Dengan Bagi Hasil Bank Syariah (Studi PT Bank Maybank Tbk dan PT Bank BRI Syariah Tbk) - Budi Rustandi Kartawinata; Candra Wijayangka; Muhammad Hasan Rabbani (Komunitas Dosen Indonesia, 2019)
Financial institutions divided into two, conventional banking and sharia banking. The fundamental thing that distinguishes between conventional and sharia financial institutions lies in the return and profit sharing provided by customers to financial institutions and / or provided by financial institutions to customers (Muhamad, 2014). Operational activities of sharia banks use the Profit Sharing Principle. This research was conducted in order to find out Revenues comparison between interest given by Bank Maybank with Profit Sharing given by Bank BRI Syariah. The purpose of this study is to find out whether there is a difference between the ratio of Revenue and analyze which greater revenue gave from Bank Maybank Interest to Profit Sharing gave from Bank BRI Syariah. The research method used in this research is qualitative method, and data collection technique using secondary data which researcher use data of financial report at bank Maybank and BRI Syariah for saving from 2012-2016. Data analysis technique used in this study is by using T test, which divided into three, normality test, homogeneity test and independent test. The revenues comparison between conventional bank interests were different to profit sharing given by sharia bank. Profit sharing given by Syariah Bank is greater because Conventional Bank uses tier system while Syariah Bank does not